Restriction analysis and sequencing of the ITS regions and 5.8S gene of rDNA of Ganoderma isolates from infected oil palm and coconut stumps in Malaysia - Latiffah, Z.; Harikrishna, K.; Tan, S.G.; Tan, S.H.; Abdullah, F.; Ho, Y.W. (Wiley, 2002)
Restriction analysis and sequencing of the ITS regions and 5.8S gene of rDNA were conducted on 53 Ganoderma isolates from infected oil palm and 15 isolates from coconut stumps to determine their relatedness. Restriction patterns of the ITS regions and 5.8S gene using seven restriction enzymes, namely, HindIII, EcoRI, BamHI, HaeIII, MspI, TaqI and AluI did not produce any patterns that could distinguish between Ganoderma isolates from infected oil palm and coconut stumps. Variations of restriction patterns were observed within and between the two groups of Ganoderma which showed that the isolates were genetically heterogeneous. Based on the dendrogram from cluster analysis of the restriction patterns, the Ganoderma isolates from infected oil palm and coconut stumps were clustered together, indicating a close relationship. Phylogenetic analysis of the nucleotide sequence of the ITS regions and 5.8S gene of 12 Ganoderma isolates using parsimony and distance methods also showed that the two groups of Ganoderma did not cluster separately. Based on the present study, the Ganoderma isolates from infected oil palm and coconut stumps were indistinguishable and closely related which suggests that the coconut stumps in oil palm plantings may have an important role in disease development.